2014
DOI: 10.1371/journal.pone.0088441
|View full text |Cite
|
Sign up to set email alerts
|

T Follicular Helper Cells and Regulatory B Cells Dynamics in Systemic Lupus Erythematosus

Abstract: T follicular helper (Tfh) cells aid effector B cells, and augment autoimmunity, whereas the role of Tfh cells on regulatory B (Breg) cells in systemic lupus erythematosus (SLE) is not known. The aim of this study is to investigate the percentage of Breg cells in SLE, and the role of Tfh cells on Breg cells. First, we demonstrated the presence of Breg cells in SLE peripheral blood mononuclear cells and in involved skins. Both the percentage of circulating Breg cells and the ability to produce interleukin-10 (IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 38 publications
(73 reference statements)
5
71
0
Order By: Relevance
“…The regulation of T FH frequency, and by extension the regulation of their impact on GC B-cell development and function, is vital to the quality of the humoral immune response (5). While the presence of too few T FH may lead to abortive GC formation and defective B-cell responses, an over-expansion was found to be associated with the prevalence of autoantibodies (6, 7). It is possible that an expansion of T FH also lowers the selection pressure on GC B-cells and leads to the emergence of low-affinity B-cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…The regulation of T FH frequency, and by extension the regulation of their impact on GC B-cell development and function, is vital to the quality of the humoral immune response (5). While the presence of too few T FH may lead to abortive GC formation and defective B-cell responses, an over-expansion was found to be associated with the prevalence of autoantibodies (6, 7). It is possible that an expansion of T FH also lowers the selection pressure on GC B-cells and leads to the emergence of low-affinity B-cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Once this subset of T cells fails to discriminate self-reactive B cells from the normal antigen-specific B cells, high-affinity autoantibodies would be generated, and thereby autoimmune disease would happen (23). Increasing evidences have shown that TFH cells play an important role in the pathogenesis of autoimmune diseases, such as SLE, RA and IgA nephropathy (17,24,25). Furthermore, researchers revealed that the frequency and higher expression of TFH cells correlate with the disease severity which might involve in the pathogenesis of MG (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Rebampide treatment reduced the number of TFH cells, but increased the number of Breg cells, similar to our results. However, one study reported that TFH cells promoted IL‐10 production during the differentiation of Breg cells in systemic lupus erythematosus . Therefore, the increase in Breg cells may be due to feedback regulation.…”
Section: Discussionmentioning
confidence: 99%